Analisis Layanan Pelanggan PT PLN Berdasarkan Media Sosial Twitter Dengan Menggunakan Metode Naïve Bayes Classifier - Tri Prasetyo Prast; Hadi Zakaria; Pandu Wiliantoro (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Services for power and energy are currently still managed by a company from the State Electricity Company (PLN), which is one of the companies within the scope of State-Owned Enterprises (BUMN). Company PT. This PLN has the aim of serving the public interest and maintaining the quality and quality of power and energy itself. By being oriented to customer satisfaction, PT. PLN will always maintain quality so that the profits get bigger every time. Public opinion is divided into negative opinions containing public complaints, positive opinions containing community support, then neutral opinions containing reports or complaints from the public. The keywords used to capture public responses and opinions on PT PLN services in the web scraping process are using keywords, namely pln tangerang district", "pln tangerang city", "pln tangerang south", "pln banten. Based on research that has been done with sentiment analysis through the use of twitter based on tweets that have been carried out using the nave Bayes classifier method with more than 80% accuracy results.